THE MODERNIZATION OF ISLAMIC EDUCATION: AZYUMARDI AZRA'S PERSPECTIVE - Abdur Rosid; Ahmad Sahidah; Amin Said Husni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research began with numerous discussions on the relationship between education and modernization in various Islamic communities. Azyumardi Azra, as an educator, provides a different perspective on the modernization of Islamic education compared to the thoughts that are usually used as references. The main objectives of this research are to examine (1) What is Azyumardi Azra's perspective on the concept of Islamic education; (2) What is Azyumardi Azra's view on modernization in Islamic education; (3) How modernization relates to elements of Islamic education, such as goals, curriculum, and educational institutions. The method applied in this research is library research, by analyzing relevant texts regarding Azyumardi Azra's thoughts on Islamic education. The data is processed through content analysis, which aims to find the meaning of the thoughts of these figures from an internal-textual and external-textual perspective, while paying attention to the socio-historical context that underlies their thoughts, so that objective conclusions can be drawn regarding views on the modernization of Islamic education in general. The findings of this study indicate that (1) Azyumardi Azra views Islamic education as a process of individual formation based on the teachings of Allah given to Muhammad SAW to become a caliph and achieve happiness in this world and the hereafter; (2) Azyumardi Azra views the modernization of Islamic education as an effort to reformulate Islamic educational thinking and reorganize systems and institutions to fit the concept of modernity that is in harmony with Islamic principles; (3) Azyumardi Azra believes that modernization in the aspect of Islamic education is closely related to the goals, curriculum, and institutions of education.